Antioxidant Activity of Some Selected East Borneo Plants - Islamudin Ahmad; Risky Sulistiarini; Laode Rijai (International Journal of Public Health Science (IJPHS), 2015)
The native plants of East Borneo the Costus specious (Koening) J.E. Smith stem, Lagerstroema spesiosa Pers leaf, Cerbera mangans L leaf, Vitis trifolia L fruit., Scurrula atropurpurea (Blume) Danser root, Brucea javanica (L.) Merr. leaf, Lygodium microphyllum, Bidens Chinensis Willd., Sonneratia caseolaris L. peel, Sonneratia caseolaris L. stem is almost under-explored for their potensial benefits. They were extracted by the solvents of increasing polarity (n-hexane, ethyl acetate, and n-butanol) were tested for their free radical activity against DPPH (2,2-diphenyl-1-picrylhydrazyl). The ethyl acetate extract of Costus spesiosus (Koening) J. E. Smith antioxidant were screnned concentration of 68 ppm, similarly athyl acetate extract of Vitis trivolia L., showed antioxidant activity at 64,30 ppm. As the ethyl acetate extract of Scurrulla atropurpurea (Blume), Brucea javanica (L.) Merr, Lygodium microphyllum and Sonneratia caseolaris L. stem, showed antioxidant activity at 273,52 ppm, 91,12 ppm, 17,39 ppm and 7,03 ppm. N-butanol extract of Lagerstroema spesiosa Pers, Cerbera mangans L, Bidens chinensis Willd, and Sonneratia caseolaris L. peel showed 8,37 ppm, 128,59 ppm, 18,17 ppm and 54,29 ppm antioxidant activity using DPPH model systems. Owing to the property, the studies can be further extended to exploit them for their possible application for preservation of food products as well as their use as health supplements.